-4(-5-b)=13(b+16)

Simple and best practice solution for -4(-5-b)=13(b+16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-5-b)=13(b+16) equation:



-4(-5-b)=13(b+16)
We move all terms to the left:
-4(-5-b)-(13(b+16))=0
We add all the numbers together, and all the variables
-4(-1b-5)-(13(b+16))=0
We multiply parentheses
4b-(13(b+16))+20=0
We calculate terms in parentheses: -(13(b+16)), so:
13(b+16)
We multiply parentheses
13b+208
Back to the equation:
-(13b+208)
We get rid of parentheses
4b-13b-208+20=0
We add all the numbers together, and all the variables
-9b-188=0
We move all terms containing b to the left, all other terms to the right
-9b=188
b=188/-9
b=-20+8/9

See similar equations:

| -9⁄8w=-2 | | a+6/4=3 | | 0=-1+n/1 | | 6z-8z=2 | | 3=n/9+4 | | 3(5x+11)=4(2x+1) | | 4y”+24y”+37y=0 | | 3a-3(7+5a)=-9(-2+a) | | 9x^2+29x+23=0 | | 4m+5/5=2m+7/7 | | 4y”+24y’+37y=0 | | 12x+10=4x+3 | | 8x=1-1 | | 117-x=199 | | 9v-v=40 | | C=8u^2-176u+1800 | | -9x+(-2x)=42 | | 72+(2y-18)=180 | | 45+2y=180 | | 3k=-25.5 | | -7x+3+7x=45 | | 2t+9=9t+8 | | 4(x+10)+5x=100 | | 7x-3=225 | | 10/12=x/36 | | 10/x=1/3 | | 1/7=x/8 | | {8/5}^x=25/64 | | .15x=96000 | | 4^(3x-5)=256 | | 7h=-(1h-18) | | 1y-y=4-y |

Equations solver categories